SIMULATION OF AUTOMATION DEVICES ON THE MEMORY ELEMENTS WITH A SUBSTANTIAL NON-LINEAR DWELL - Andrieievskikh, O. V. (Science and Transport Progress, 2004)
The paper proposes a computer method of modelling automatic devices, based on the memory elements with essential nonlinear delays, both with and without fixation of influence. In the procedure of memory elements modelling, performed on electromagnetic devices, remembering the previous influence, it is proposed to use a multi-cycle substitution scheme. Depending on the required accuracy, the model can use up to four delay channels with different number of single-cycle logic elements of memory per one memory element, and one internal memory element, based on a J-K trigger. The expressions have been provided, determining the model’s output signals, with account of the time of reaction upon the input influence and upon the commutation of executive circuit. The findings have been illustrated by an example